The Effect of Work Motivation, Work Environment, Work Discipline on Employee Satisfaction and Public Health Center Performance - Suprapti, Suprapti; Astuti, Jannah Puji; Sa'adah, Noor; Rahmawati, Salis Diah; Astuti, Rulyta Yuli; Sudargini, Yuli (AGUSPATI Research Institute, 2020)
The pupose of this study is to analyze the effect of work motivation on employee satisfaction, effect of work environment on employee satisfaction, effect of work discipline on employee satisfaction effect of work motivation on public health center Performance, effect of work environment on public health center Performance, effect of work discipline on public health center Performance, effect of employee satisfaction on public health center performance. The method used in this research is quantitative method. Data was collected by distributing questionnaires to 80 permanent employees of public health center . For questions / statements about the identity of respondents designed in the form of a semi-open questionnaire in addition to a closed questionnaire. Data collection technique is using questionnaire with Likert Scale. Analysis from this study is using SEM (Structural Equation Model) with SmartPLS version 3.0 as a statistic tools. Based on the results of data analysis through a questionnaire distributed to respondents, found several conclusions as follows There is a significant effect of work motivation on employee satisfaction, there is a significant effect of work environment on employee satisfaction, there is a significant effect of work discipline on employee satisfaction,there is a significant effect of work motivation on public health center Performance, there is a significant effect of work environment on public health center Performance,there is a significant effect of work discipline on public health center Performance,there is a significant effect of employee satisfaction on public health center performance.